Efficacy and Safety of Sarilumab in Hospitalized Patients With Coronavirus Disease 2019: A Randomized Clinical Trial. (26th February 2022) - Sivapalasingam, Sumathi; Lederer, David J; Bhore, Rafia; Hajizadeh, Negin; Criner, Gerard; Hosain, Romana; Mahmood, Adnan; Giannelou, Angeliki; Somersan-Karakaya, Selin; O'Brien, Meagan P; Boyapati, Anita; Parrino, Janie; et al.
Abstract: Background: Open-label platform trials and a prospective meta-analysis suggest efficacy of anti–interleukin (IL)-6R therapies in hospitalized patients with coronavirus disease 2019 (COVID-19) receiving corticosteroids. This study evaluated the efficacy and safety of sarilumab, an anti–IL-6R monoclonal antibody, in the treatment of hospitalized patients with COVID-19. Methods: In this adaptive, phase 2/3, randomized, double-blind, placebo-controlled trial, adults hospitalized with COVID-19 received intravenous sarilumab 400 mg or placebo. The phase 3 primary analysis population included patients with critical COVID-19 receiving mechanical ventilation (MV). The primary outcome was proportion of patients with ≥1-point improvement in clinical status from baseline to day 22. Results: There were 457 and 1365 patients randomized and treated in phases 2 and 3, respectively. In phase 3, patients with critical COVID-19 receiving MV (n = 298; 28.2% on corticosteroids), the proportion with ≥1-point improvement in clinical status (alive, not receiving MV) at day 22 was 43.2% for sarilumab and 35.5% for placebo (risk difference, +7.5%; 95% confidence interval [CI], –7.4 to 21.3; P =.3261), a relative risk improvement of 21.7%. In post hoc analyses pooling phase 2 and 3 critical patients receiving MV, the hazard ratio for death for sarilumab vs placebo was 0.76 (95% CI, .51 to 1.13) overall and 0.49 (95% CI, .25 to .94) in patients receiving corticosteroids at baseline. Conclusions: This study did not establish the efficacy of sarilumab in hospitalized patients with severe/critical COVID-19. Post hoc analyses were consistent with other studies that found a benefit of sarilumab in patients receiving corticosteroids. Clinical Trials Registration: NCT04315298. Abstract : Sarilumab did not lead to significant improvements in clinical status or mortality in hospitalized patients with coronavirus disease 2019, most of whom were not receiving corticosteroids. However, there may be benefit of anti–interleukin-6R therapy in patients receiving corticosteroids.